Gender Role Transformation in The Position of Marriage Registration Officer: A Comparative Study of Islamic Family Law in Indonesia and The Muslim World - Andre Afrilian; Zaenul Mufti; Khairul Akmal (SiRad: Pelita Wawasan, 2025)
The role of the Marriage Registration Officer (PPN) is considered very important in the KUA agency because marriage is a sacred event in order to protect the dignity and sanctity, especially of women and aims to provide legal certainty and control over personal interests and social life of the community, therefore it needs to be recorded and it becomes a valid requirement for marriage for the state as Paragraph 2 Article 2 of Law No. 1 of 1974 concerning Marriage. However, in the implementation mechanism, marriage registration officials in Indonesia have only focused on men, and it is questionable whether women can also carry out this task considering that in reality today there are equal rights and obligations between women and men in various spheres of social life. In this case, some people think that Indonesia and several other Islamic countries still do not apply gender equality in their social life which has been applied in several Islamic countries such as Morocco, Egypt and Turkey. The research method used in this research is descriptive-analytical techniques and library research and uses a gender and comparative studies approach that focuses on comparing legal systems and practices in various countries to understand the differences and similarities in the acceptance and implementation of the role of women as Marriage Registrar Employees. The results of this study are the values that motivate some Islamic countries not to make women as marriage registrars such as different madhhabs or different views on the concept of gender in several Islamic countries. [Peranan Pegawai Pencatat Nikah (PPN) dinilai sangat penting dalam instansi KUA karena pernikahan merupakan peristiwa sakral dalam rangka melindungi martabat dan kesucian terutama para wanita dan bertujuan untuk memberikan kepastian hukum dan kontrol terhadap kepentingan pribadi dan kehidupan bersosial masyarakat, oleh karenanya perlu dicatat dan itu menjadi sayarat sahnya pernikahan bagi negara sebagaimana Ayat 2 Pasal 2 Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan. Namun dalam mekanisme pelaksanaannya pegawai pencatat nikah di Indonesia hingga kini hanya berkutat kepada laki-laki, dan menjadi pertanyaan apakah wanita juga bisa mengemban tugas tersebut mengingat realitanya dewasa ini terdapat persamaan hak dan kewajiban antara wanita dan laki-laki dalam berbagai lingkup kehidupan bersosial. Dalam hal ini sebagian orang beranggapan bahwa Indonesia dan beberapa negara Islam lainnya masih belum menerapkan gender equality dalam kehidupan sosialnya dimana telah diterapkan di beberapa negara Islam seperti Maroko, Mesir dan Turki. Metode penelitian yang digunakan dalam penelitian ini ialah dengan teknik deskriptif-analitis dan studi pustaka (library research) dan menggunakan pendekatan studi gender dan komparatif yang fokus pada perbandingan sistem hukum dan praktik di berbagai negara untuk memahami perbedaan dan persamaan dalam penerimaan dan pelaksanaan peran wanita sebagai Pegawai Pencatat Nikah. Adapun hasil dari penelitian ini adalah adanya nilai-nilai yang melatarbelakangi beberapa negara Islam untuk tidak menjadikan wanita sebagai pencatat nikah seperti berbedanya mazhab atau berbedanya pandangan terhadap konsep gender di beberapa negara Islam.]